2017
DOI: 10.1038/nrdp.2017.55
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoparathyroidism

Abstract: Hypoparathyroidism is a disease characterized by inadequately low circulating concentrations of parathyroid hormone (PTH) resulting in low calcium levels and increased phosphate levels in the blood. Symptoms of the disease result from increased neuromuscular irritability caused by hypocalcaemia and include tingling, muscle cramps and seizures. The most common cause of the disease is inadvertent removal of, or injury to, the parathyroid glands during neck surgery, followed by genetic, idiopathic and autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
208
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(222 citation statements)
references
References 167 publications
5
208
1
8
Order By: Relevance
“…Indeed, subjects with CAN often complain symptoms such as exercise intolerance and weakness, (26) as well as patients with hypoPT do. (2) Our hypothesis seems to be supported by previous studies that have demonstrated a relationship between fatigue and autonomic dysfunction during different chronic diseases, namely Parkinson's disease, (27) multiple sclerosis, (28) and chronic fatigue syndrome. (29) Evaluations of fatigue have not yet been performed, and therefore, we are conducting further analyses to investigate the relationship between fatigue and CAN.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Indeed, subjects with CAN often complain symptoms such as exercise intolerance and weakness, (26) as well as patients with hypoPT do. (2) Our hypothesis seems to be supported by previous studies that have demonstrated a relationship between fatigue and autonomic dysfunction during different chronic diseases, namely Parkinson's disease, (27) multiple sclerosis, (28) and chronic fatigue syndrome. (29) Evaluations of fatigue have not yet been performed, and therefore, we are conducting further analyses to investigate the relationship between fatigue and CAN.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the worsening of CAN in our population with lower calcium levels may highlight the importance of calcium in the development of autonomic neuropathy. It has been demonstrated that low calcium level determines an increase of neuromuscular irritability and hypocalcemia increases the probability of triggering action potentials in the membrane of a neuron …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoparathyroidism, in particular ADH1, is a disease for which there remains a need for better therapeutics . Given that ADH1 results from gain‐of‐function mutations in the CAR , negative allosteric modulators of the CaR, calcilytics, represent a rational, precision medicine approach to treating this disease.…”
Section: Discussionmentioning
confidence: 99%